THERAPEUTIC EFFICACY OF DIFFERENT ANTHELMINTICS IN FASCIOLOSIS AFFECTED GOATS OF SOUTH GUJARAT - Shirmali, RG; Patel, MD; Rathod, PH; Patel, RM (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Efficacy of three anthelmintics against fasciolosis in goats was evaluated based on clinical scores and qualitative as well as quantitative examination of faecal samples. A total of 40 fasciolosis affected anaemic goats having more than 100 egg per gram (EPG) of faeces were randomly allotted to four different treatment groups with 10 goats in each. The efficacy of Closental alone, Triclabendazole + Ivermectin and Oxyclozanide + Levamisole + Silymarine was evaluated in group-I, II and III, respectively, by administering with oral standard dose rate of 15.0, 10.2 and 10.0 mg/kg body wt once, respectively, whereas goats of group-IV were kept as untreated control. Based on egg per gram, the efficacy of Closental alone, Triclabendazole + Ivermectin and Oxyclozanide + Levamizole+ Silymarine was 99.63, 100.00 and 94.74%, respectively, on 7th day and 100.00, 100.00 and 97.38% on 30th day post-treatment, respectively. The results were also positively correlated with improvement in FAMACHA score, body condition score as well as haemoglobin concentration and packed cell volume. Therefore, it is concluded that an early diagnosis and treatment with newer drugs for fasciolosis in goats could be advised to reduce economic losses due to their better efficacy on fasciolosis.
Keywords: Anthelmintics; Efficacy; Egg per gram; Clinical response; Fasciolosis; Goats